The lost manuscript of Frďřic Cailliaud : arts and crafts of the ancient Egyptians, Nubians, and Ethiopians - Cailliaud, Frďřic, 1787-1869; Bednarski, Andrew; Mainterot, Philippe, writer of supplementary textual content (Cairo, New York : The American University in Cairo Press, 2014)
Includes bibliographical references (pages 280-288) and index.